Migratory destinations of humpback whales from Norwegian and adjacent waters: evidence for stock identity - T. Stevick, Peter; 0ien, Nils; K. Mattila, David (J. Cetacean Res. Manage., 1999)
Migratory destinations of humpback whales (Megaptera novaeangliae) in the eastern North Atlantic were investigated using natural markings. A total of 96 individuals was identified from Norwegian and adjacent waters during 1992 and 1993: of these 63 were observed in the Norwegian and Barents Seas and 33 in the Greenland Sea near Jan Mayen. These were compared with other individuals identified throughout the North Atlantic to identify resightings. Ten individuals were identified in both Norway and in the West Indies. There were no significant differences in this rate of exchange to the West Indies between the sample from Norway or either Norwegian sub-area and other feeding areas in the North Atlantic. The mean West Indies sighting date for humpback whales from Norway was 2 March, significantly later than the overall mean for sightings from the West Indies. The individuals identified represent a variety of reproductive classes and both sexes. Observations of mothers with newborn calves, and males in competitive groups, provide the strongest evidence to date that the West Indies is utilised as a breeding and calving ground by humpback whales which feed in Norwegian waters. These results suggest that the West Indies is an important, and likely the primary, breeding destination for individual humpback whales feeding off Norway.